Effect of 12-week SPARQ training on the ability of youth football players - Zhou, Yuhang; Tai, Feng; Yu, Shibo (Sportverletzung · Sportschaden, 2024)
Aim To evaluate the effect of a 12-week physical training regime comprising five components – speed, power, agility, reaction, quickness – on young football players’ performance in terms of their capacity to move quickly in different phases.Methods The football players were randomly divided into an experimental group (n = 12) and a control group (n = 12). The rapid change of direction mobility was systematically investigated by using outdoor tests, the Illinois 505 Agility Test, the Square Pace Test, the Nebraska Agility Test, and the T-Shape Agility Test.Results With the intervention of training, considerable improvements were detected in all indicators, with the SPARQ training approach outperforming.Conclusion The combined results indicate that SPARQ training can deliver favourable efficiency in terms of enhancing the agility of young football players.
Keywords: Youth football players; SPARQ training; direction mobility; agility